Effects of recovery type after a judo combat on blood lactate removal and on performance in an intermittent anaerobic task - Franchini, E.; Takito, M. Y.; Nakamura, F. Y.; Matsushi, (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The objective of this study was to verify the effects of active (AR) and passive recovery (PR) after a judo match on blood lactate removal and on performance in an anaerobic intermittent task (4 bouts of upper body Wingate tests with 3-min interval between bouts; 4WT). Methods: The sample was constituted by 17 male judo players of different competitive levels: A) National (Brazil) and International medallists (n. 5). B) State (São Paulo) medallists (n. 7). C) City (São Paulo) medallists (n. 5). The subjects were submitted to: 1) a treadmill test for determination of VO2peak and velocity at anaerobic threshold (VAT); 2) body composition; 3) a 5-min judo combat, 15-min of AR or PR followed by 4WT. Results: The groups did not differ with respect to: body weight, VO2peak, VAT, body fat percentage, blood lactate after combats. No difference was observed in performance between AR and PR, despite a lower blood lactate after combat (10 and 15 min) during AR compared to PR. Groups A and B performed better in the high-intensity intermittent exercise compared to athletes with lower competitive level (C). Conclusion: The ability to maintain power output during intermittent anaerobic exercises can discriminate properly judo players of different levels. Lactate removal was improved with AR when compared to PR but AR did not improve performance in a subsequent intermittent anaerobic exercise.